Saubhagya: An Online Food Donation Platform for Ending Hunger and Malnutrition in Sri Lanka - G.H.T.R. Irushika; K.V.M. Wijesinghe; P.K.I. Udeshika; J.J. Sathsara; D. I. De Silva; R.R.P. De Zoysa (Information System; Universitas Buana Perjuangan Karawang, 2023)
Hunger and malnutrition continue to be significant challenges in developing nations, including Sri Lanka. To address this issue, the research paper presents